Feeding and growth variations affect δ13C and δ15N budgets during ontogeny in a lepidopteran larva - Charberet, Samuel M.; Maria, Annick; Siaussat, David; Gounand, Isabelle; Mathieu, Jérôme (Peer Community Journal, 2023)

(untitled)
Isotopes are widely used in ecology to study food webs and physiology. The fractionation observed between trophic levels in nitrogen and carbon isotopes, explained by isotopic biochemical selectivity, is subject to important within-trophic level variations, leading to imprecision in trophic level estimation. Understanding the drivers of these variations is thus important to improve the study of food webs. In this study, we characterized this variation by submitting Spodoptera littoralis larvae to a gradient of starvation levels, a factor that we hypothesized would change the trophic fractionation between individuals. The various growth rates that were induced from these starvation levels resulted in a ∼ 1-1.5‰ within-trophic level variation of the trophic fractionation in both carbon and nitrogen, which is substantial compared to the 3-4‰ classically associated with between-trophic levels variations. Hence starved animals sampled  in natura may be ranked at a higher trophic level than they really are. We were able to gain an understanding of the effect of growth rate on isotopes fluxes between three easy-to-measure biological materials, food, the organism and its wastes (frass), giving insight into physiological processes at play but also conveying helpful information to the sampling framework of field studies.